البنية العاملية للعوامل المؤثرة على تبني تجارة التجزئة للتجارة الالكترونية في الجزائر - بريش ،فايزة (جامعة الوادي University of Eloued, 2025)
This study aimed to develop a model to identify the factors influencing the adoption of e-business in retail and the shift to e- retailing.The questionnaire was used to collect primary data by distributing 268 of them and analyzing them using the statistical software JASP V19 and AMOS V24 , employing various tests, It identifies three key factors: (1)The Organizational factors, including the institution’s attitude toward e-commerce, digitalization strategy, (2) Macro Environment, covering government support and legal aspects. (3) The Specific environment, which included pressure from suppliers and customers.
The factor structure of the factors influencing the adoption of e-commerce by retail tradein Algeria
Keywords: تجارة التجزئة; البيئة التنظيمية; Retail trade; E-retailing; The OrganizationalEnvironment; Macro Environment; Specific Environment.